Prevalence and associated factors of self-reported ischaemic heart disease and/or stroke: A cross-sectional nationally representative community-based study of adults in Malawi in 2017 - Supa Pengpid (2022)
Objective This study aimed to assess the prevalence and associated factors of self-reported ischaemic heart disease (IHD) and/or stroke among adults in Malawi. Design Population-based cross-sectional study. Setting Nationally representative sample of general adult population in Malawi. Participants The sample included 4187 persons aged 18-69 years (32 years of median age) that participated in the '2017 Malawi STEPwise Approach to Non-Communicable Disease Risk-Factor Surveillance survey.' Primary and secondary outcome measures Self-reported history of IHD and/or stroke, along with biological, behavioural, psychosocial stress and sociodemographic covariates. Multivariable logistic regression calculated OR with 95% CI for IHD and/or stroke. Results The prevalence of IHD and/or stroke was 6.5%, 4.4% among men and 8.4% among women. In adjusted logistic regression analysis, older age (50-69 years) (adjusted OR (AOR) 3.49, 95% CI 1.75 to 6.94), female sex (AOR 2.09, 95% CI 1.45 to 3.01), Chewa speaking (AOR 4.62, 95% CI 1.32 to 16.22), English speaking (AOR 5.63, 95% CI 1.43 to 22.19), suicidal ideation, plan and/or attempt (AOR 1.87, 95% CI 1.11 to 3.13) and sedentary behaviour (AOR 2.00, 95% CI 1.12 to 3.59) were associated with IHD and/or stroke. In addition, in unadjusted analysis, non-paid or unemployed, urban residence, overweight, obesity and having hypertension were associated with IHD and/or stroke. Conclusions Almost 1 in 10 women and 1 in 20 men aged 18-69 years had IHD and/or stroke in Malawi. Several risk and protective factors were found that can be targeted in population health interventions.